Physiopathological responses of sole (Solea senegalensis) subjected to bacterial infection and handling stress after probiotic treatment with autochthonous bacteria. Issue 83 (December 2018) - Peixoto, M.J.; Domingues, A.; Batista, S.; Gonçalves, J.F.M.; Gomes, A.M.; Cunha, S.; Valente, L.M.P.; Costas, B.; Ozório, R.O.A.
Abstract: This study aimed to evaluate the protective effects of four autochthonous bacteria isolated from juvenile sole ( Solea senegalensis ) intestine as dietary probiotic supplement against bacterial pathogen infection and handling/transport stressors. Growth performance and immune responses were evaluated after 85 days of feeding trial. Sole (IBW = 16.07 ± 0.11 g) were fed six experimental diets, a control diet (CTRL, without the dietary probiotic supplementation), and five diets supplemented with probiotic bacteria: PB1 ( Shewanella hafniensis ), PB2 ( Enterococcus raffinosus ), PB3 ( Shewanella hafniensis  +  Arthrobacter soli ), PB4 ( Pseudomonas protegens  +  Arthrobacter soli ) and PB5 ( Shewanella hafniensis  +  Arthrobacter soli  +  Enterococcus raffinosus ). All bacteria were selected based on their in vitro antimicrobial activity. After the growth trial, fish were submitted to a stress factor (transport) and then each dietary group was divided in two additional groups: non-infected (placebo) and infected with Photobacterium damselae subsp. piscicida . Immune and antioxidant responses were evaluated at day 10 post-infection. In infection trial A, fish were infected on the same day of transport, whereas in trial B fish were infected after a 7-day recovery from the transport stress. At the end of the feeding trial, fish fed with PB2 and PB4 showed lower final body weight when compared with the other dietary groups. Respiratory burst activity and nitric oxide production were not affected by probiotic supplementation. Fish fed with PB5 presented lower peroxidase activity compared to CTRL. Lysozyme and alternative complement pathway activity (ACH50) showed no significant differences between treatments. The innate immune responses were significantly affected after handling stress and bacterial infection. In trial A, the ACH50 levels of infected fish were significantly lower than the placebo groups. On the other hand, in trial B fish infected with Pdp demonstrated higher ACH50 levels when compared to placebos. Peroxidase levels were strongly modulated by bacterial infection and handling stress. In trials A and B, infection had a clear downgrade effect in peroxidase levels. Lipid peroxidation, catalase, glutathione S-transferase and glutathione reductase were altered by both bacterial infection and transport. Overall, dietary probiotic supplementation did not influence growth performance of sole. The immune and oxidative defenses of sole responded differently to infection depending on the probiotic and the synergy between pathogen infection and transport. Highlights: Intestine autochthonous bacteria were used as probiotic in Senegalese sole. Diets PB2 and PB4 resulted in lower final body weight compared with control. Respiratory burst and nitric oxide were not affected by probiotic supplementation. Oxidative stress and innate immunity were altered by handling and infection.